Late Triassic bivalves and brachiopods from southern Mendoza, Argentina - Damborenea, Susana Ester (2012)
The Atuel river section in southern Mendoza Province, Argentina, is one of the few South American localities where the Triassic/ Jurassic transition occurs in fully marine deposits. Bivalves and brachiopods from the poorly diverse Late Triassic macrofauna are described, most of them found below Choristoceras cf. marshi Hauer. The fauna contains 15 bivalve species and at least 5 brachiopod species recorded from several Norian?/Rhaetian fossiliferous levels at Arroyo Malo. The fauna also includes cephalopods, gastropods, a cnidarian, and some foraminifers and ostracods. Bivalves are the most diverse group, with species belonging to 13 superfamilies. Two of the bivalve species are described as new: Pseudolimea riccardii Damborenea n. sp. and Asoella campbellorum Damborenea n. sp. Only one bivalve species ranges into Early Jurassic deposits. The bivalve fauna contains mostly suspension feeder species, including deep infaunal (Pholadomya), shallow infaunal (Minetrigonia?, Nicaniella?, Palaeocardita and Septocardia) and epifaunal species (Cassianella, Liostrea, Praechlamys?, Pseudolimea and Otapiria). Following next in terms of diversity, brachiopods are represented by no fewer than three orders, and four superfamilies, one of the species being new: Bolilaspirifer riccardii Manceñido n. sp. These species are also epifaunal suspension-feeders, and from a biostratigarphical viewpoint are regarded as members of a newly proposed Assemblage Zone that supports the age correlation with similar faunas from other south Pacific areas.